MAPLES (Acer L.) IN THE STREETS OF THE CENTRAL PART OF BELGRADE - CONDITION AND FUNCTIONALITY - Stavretović, Nenad (Acta herbologica, 2023)
This research investigated the existing condition and functionality of rows of maple trees (Acer L.) (which are traditionally used in our country for greening) in the streets that are the most frequent in terms of traffic intensity, ways of use and measures to maintain greenery (streets of the I and II order) on territory of the municipality of Stari grad (Belgrade). In the investigated area ​​a total of 39 streets of these categories, rows of maple trees are represented in 2 out of 15 streets of the I order and in 10 out of 24 streets of the II order. It was determined that the total number of trees belong to the species of this genus is 735. Species of maple were recorded are: Acer pseudoplatanus L., Acer platanoides L., Acer campestre L. and Acer saccharinum L. The most represented species here is Acer pseudoplatanus L. with a total of 442 (60.13%) trees, average vitality score 3.6. They are followed: Acer platanoides L. with 213 (28.98%) recorded trees and an average vitality score of 3.5, Acer campestre L. with 72 (9.80 %) recorded trees and a rating of 3.1 and Acer saccharinum L. with 8 (1.09 %) trees and a rating of 2.3. It was found that one of the main factors in reducing the functionality of street row maple trees in the researched area is the application of a care measure, topping the trunks.